Re-Engineering the Human Resource Strategies Amid and Post-Pandemic Crisis: Probing into the Moderated Mediation Model of the High-Performance Work Practices and Employee's Outcomes - Zhiqiang, Ma; Khan, Hira Salah ud din; Chughtai, Muhammad Salman; Mingxing, Li (Frontiers in Psychology, 2021)
By incorporating the conservation of resources theory, this study examines how high-performance work practices affect the employee’s in-role performance and task performance during the COVID-19 pandemic. Further, this study investigates how organization-based self-esteem and positive psychological capital affect the relationship between high-performance work practices and employee outcomes such as employee’s in-role performance and task performance. A quantitative technique based on the survey method was used to gather the investigation's primary data. Two hundred and eleven bank employees working in different banks of Punjab, Pakistan participated in the survey process. PROCESS-macros was used to test the relationship among the study constructs. Our results supported all the study hypotheses except the moderated mediated impact of positive psychological capital; organization-based self-esteem was not supported. This study is the first of its kind that focuses on high-performance work practices and employee outcomes amidst the COVID-19 pandemic in a developing country, Pakistan. This study's findings provide practical implications in the post and continuing pandemic situation for organizations to for human resource management to redesign workforce strategies to increase their contribution and responses to realize organizational priorities. Though researchers have explored the topic in different sectors, scant studies have investigated the potential impact, barriers, and enabling mechanisms’ that functions as a catalyst in high-performance work practices during the pandemic situation.